Sustainable Technologies, Policies, and Constraints in the Green Economy - Vasile, Andrei Jean (Information Science Reference, 2015)
This book carefully investigates the complex issues that surround the wide array of concepts, policies, and measures that come into play when promoting this somewhat new ideology.